Phytoplankton Orientation in a Turbulent Ocean: A Microscale Perspective - Basterretxea, G.; Font-Muñoz, J. S.; Tuval, I. (Frontiers in Marine Science, 2020)
Phytoplankton are by definition autotrophic microorganisms that passively drift with fluid motion. Accordingly, the traditional view of a turbulence-homogenized phytoplankton distribution in the ocean, where cells randomly organize and interact, is deeply rooted in biological oceanography studies. However, increasing understanding of microscopic processes in the ocean is revealing a world of microscale patterns resulting from cell behaviors and fluid-cell interactions that challenges this vision. Autotrophic cells have developed active (i.e. flagella) and passive (i.e. morphological structures, vesicles) motility mechanisms that allow them different degrees of spatial control. Their complex interaction with the ocean physicochemical landscape commonly results in small-scale spatial heterogeneities and non-isotropic orientations that can strongly influence ecosystem level processes. Cell orientation, in particular, is fundamental for key biological functions such as sensing, metabolism, locomotion, chain formation or sexual reproduction. Moreover, preferential alignment of elongated cells can modulate the propagation of light through the ocean and is fundamental for accurate interpretation of remote sensing data. Innovative observational and experimental techniques (e.g. in situ holography, laser diffractometry, etc.) allowing the subtle analysis of cell-fluid interactions are revealing that, at the microscopic level, organisms present well defined orientation and interaction patterns under prevalent conditions in the sea. Thus, the interplay of biology, fluid dynamics, and optics may shape, by means of anisotropic cell distributions, pivotal cross-scale aspects of phytoplankton ecology.